Causality between exports and growth : a study of Singapore and United States - Tan, Shiau Tse (2014)
In this study, the relationship and causality between export growth and GOP growth, which is a proxy for economic growth, is tested using Singapore and United States as samples. The exports and GDP variables were first tested to see if they are cointegrated. The result was that for both countries, no cointegration property was found. Standard Granger test was then used to test for causality between exports and GDP growth.